An exploration of the interrater agreement of visual analysis with and without context - Ford, Andrea L B; Rudolph, Brenna N; Pennington, Brittany; Byiers, Breanne J (Journal of applied behavior analysis, 2020)
Visual analysis is integral to the analysis of single-case experimental design (SCED) data. Previous studies have shown that many factors may influence the interrater agreement (IRA) of visual analysis. One factor that has received little direct attention is the impact of contextual information. In the current study, authors of recently published SCED studies were asked to make judgments regarding functional relations based on published datasets that met criteria for design quality. Respondents were randomly assigned to view graphs with or without contextual information and the degree of interrater agreement was compared. Results revealed that contextual information had no impact on IRA for decisions of a functional relation. IRA was high across both groups for 6 of the 7 datasets examined. Implications and recommendations based on these results are discussed.